The Climate-Smart Agriculture Papers Investigating the Business of a Productive, Resilient and Low Emission Future - Rosenstock, Todd S.; Nowak, Andreea; Girvetz, Evan (Springer Nature, 2019)
Environment; Environmental management; Agriculture; Climate change; Soil science; Soil conservation; Environmental law; Environmental policy